2005
DOI: 10.1038/ja.2005.76
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal and Triterpenoidal Fungal Metabolites as Ligands of Liver X Receptors

Abstract: Cholesterol homeostasis is tightly controlled process that involves a variety of regulators including liver X receptors (LXR). Agonists of LXR are expected to increase cholesterol efflux, lower LDL, and raise HDL levels. Screening of a natural product library of microbial extracts using a LXR-scintillation proximity assay (SPA) binding assay and bioassay-guided fractionation of a number of fungal extracts led to the isolation of five ergostane and a cycloartane derivative. These compounds exhibited IC 50 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
0
16
0
2
Order By: Relevance
“…Another cholesterol-derived molecule, follicular fluid Nuclear Receptors and Their Selective Modulators meiosis activating sterol, is also a potent activator of LXRa. Desmosterol, 6a-hydroxylated bile acids, and various compounds derived from plants and fungi are also potent activators of LXR (Song et al, 2000;Huang et al, 2005;Jayasuriya et al, 2005;Ondeyka et al, 2005;Yang et al, 2006). LXR is widely known to be targeted by two nonsteroidal synthetic agonists: T0901317 [N-[4-(1,1,1,3,3,3-hexafluoro-2-hydroxypropan-2-yl)phenyl]-N-(2,2,2-trifluoroethyl)benzenesulfonamide] and GW3965 [2-[3-[3-[[2-chloro-3-(trifluoromethyl)phenyl]methyl-(2,2-diphenylethyl)amino]propoxy]phenyl]acetic acid] (Fig.…”
Section: Selective Liver X Receptor Modulatorsmentioning
confidence: 99%
“…Another cholesterol-derived molecule, follicular fluid Nuclear Receptors and Their Selective Modulators meiosis activating sterol, is also a potent activator of LXRa. Desmosterol, 6a-hydroxylated bile acids, and various compounds derived from plants and fungi are also potent activators of LXR (Song et al, 2000;Huang et al, 2005;Jayasuriya et al, 2005;Ondeyka et al, 2005;Yang et al, 2006). LXR is widely known to be targeted by two nonsteroidal synthetic agonists: T0901317 [N-[4-(1,1,1,3,3,3-hexafluoro-2-hydroxypropan-2-yl)phenyl]-N-(2,2,2-trifluoroethyl)benzenesulfonamide] and GW3965 [2-[3-[3-[[2-chloro-3-(trifluoromethyl)phenyl]methyl-(2,2-diphenylethyl)amino]propoxy]phenyl]acetic acid] (Fig.…”
Section: Selective Liver X Receptor Modulatorsmentioning
confidence: 99%
“…Later these authors reported the identification of its C-4 epimer . Cycloeucalenone has also been described as produced from fungus source (Ondeyka et al, 2005) and from Tinospora crispa (Menispermaceae) (Kongkathip et al, 2002). In this last work 1 was tested as cardiac contractile agent.…”
Section: Resultsmentioning
confidence: 99%
“…(7) displayed non selective binding affinity with IC 50 values of 0.5 and 1.0 μM, respectively, for LXR and , thus pointing toward the positive effect on selectivity played by the presence of the methyl group at C-24 and/or the lack of the C-29 methyl group. However, this compound was not an agonist at 10 μM against either of the two receptors and was not effective in the transactivation assays [252].…”
Section: Liver X Receptor (Lxr): Functions and Natural Ligandsmentioning
confidence: 99%